Expression and functional significance of VE-cadherin in aggressive human melanoma cells: Role in vasculogenic mimicry - Hendrix, Mary J. C. (The National Academy of Sciences, 2001)
We recently have introduced the term vasculogenic mimicry to describe the unique ability of aggressive melanoma tumor cells to form tubular structures and patterned networks in three-dimensional culture, which “mimics” embryonic vasculogenic networks formed by differentiating endothelial cells. In the current study, we address the biological significance of several endothelial-associated molecules (revealed by microarray analysis) with respect to expression and function in highly aggressive and poorly aggressive human cutaneous melanoma cell lines (established from the same patient). In a comparative analysis, CD31 was not expressed by any of the melanoma cell lines, whereas TIE-1 (tyrosine kinase with Ig and epidermal growth factor homology domains-1) was strongly expressed in the highly aggressive tumor cells with a low level of expression in one of the poorly aggressive cell lines. Vascular endothelial (VE)-cadherin was exclusively expressed by highly aggressive melanoma cells and was undetectable in the poorly aggressive tumor cells, suggesting the possibility of a vasculogenic switch. Down-regulation of VE-cadherin expression in the aggressive melanoma cells abrogated their ability to form vasculogenic networks and directly tested the hypothesis that VE-cadherin is critical in melanoma vasculogenic mimicry. These results highlight the plasticity of aggressive melanoma cells and call into question their possible genetic reversion to an embryonic phenotype. This finding could pose a significant clinical challenge in targeting tumor cells that may masquerade as circulating endothelial cells or other embryonic-like stem cells.